Mutation‐enhanced international prognostic systems for essential thrombocythaemia and polycythaemia vera. (16th January 2020) - Tefferi, Ayalew; Guglielmelli, Paola; Lasho, Terra L.; Coltro, Giacomo; Finke, Christy M.; Loscocco, Giuseppe G.; Sordi, Benedetta; Szuber, Natasha; Rotunno, Giada; Pacilli, Annalisa; Hanson, Curtis A.; Ketterling, Rhett P.; et al.
Summary: Survival prediction in essential thrombocythaemia (ET) and polycythaemia vera (PV) is currently based on clinically‐derived variables; we examined the possibility of integrating genetic information for predicting survival. To this end, 906 molecularly‐annotated patients (416 Mayo Clinic; 490 University of Florence, Italy), including 502 ET and 404 PV, were recruited. Multivariable analysis identified spliceosome mutations to adversely affect overall ( SF3B1, SRSF2 in ET and SRSF2 in PV) and myelofibrosis‐free ( U2AF1, SF3B1 in ET) survival; TP53 mutations predicted leukaemic transformation in ET; "adverse" mutations occurred in 51 (10%) ET and 8 (2%) PV patients. We confirmed the independent survival effect of adverse mutations [hazard ratio (HR) 2·4, 95% CI 1·6–3·5], age >60 years (6·6, 4·6–9·7), male sex (1·8, 1·3–2·4) and leukocytosis ≥11 × 10 9 /l (1·6, 1·1–2·2), in ET, and adverse mutations (7·8, 3·1–17·0), age >67 years (5·4, 3·6–8·1), leukocytosis ≥15 × 10 9 /l (2·8, 1·8–4·2) and thrombosis history (2·0, 1·4–2·9), in PV. HR‐based risk point allocation allowed development of three‐tiered mutation‐enhanced international prognostic systems (MIPSS) which were validated in both cohorts and performance was shown to be superior to conventional scoring systems. Spliceosome mutations enhance survival prediction in ET and PV and identify patients at risk for fibrotic progression. TP53 mutations predict leukaemic transformation in ET.